THE IMPACT OF ENDOPHYTE BACTERIA APPLICATIONS ON GROWTH AND YIELD OF PEANUT (Arachis hypogeae L.) - Retno Tri Purnamasari (Gontor AGROTECH Science Journal, 2018)
The purpose of this research was to find out the impact of endophyte bacteria applications on the growth and yield of peanut crops. The research was conducted at Jl. Pahlawan No.55 C, Pasuruan with altitude of ± 14 m asl with an average temperature of  29ºC - 34ºC in April-July 2017. This research used Randomized Completely Block Design with the treatment of endophyte bacteria dose consists of four level that is: A0= without endophyte bacteria, A1= endophyte bacteria 10 ml, A2= endophyte bacteria 20 ml and A3= endophyte bacteria 30 ml.This research was conducted that the endophyte bacteria 20 ml in peanuts that is able to deliver growth and yield on all parameters of observation. The highest production was in endophyte bacteria 20 ml which 65,52 g plot-1, followed by endophyte bacteria 10 ml which produce 35,93 g plot-1, then 30 ml endophyte bacteria which produce 26,74 g plot-1 and without endophytic bacteria giving the lowest yield which produce 16,38 g plot-1.